Imaging Strategies for Rectal Cancer Initial Staging: Does Pelvic Computed Tomography Provide Significantly Additional Findings when High-resolution Magnetic Resonance Imaging has Been Performed? - Liu, Li-Yan; Liu, Li-Heng (Current Medical Imaging, 2020)
Background: Initial staging of rectal cancer is done by high-resolution magnetic resonance imaging (MRI), however, pelvic computed tomography (CT) is also frequently used. The aim of this study was to evaluate the added clinical benefit of pelvic CT or whether it can alter the initial staging or not. Methods: The study was composed of 187 patients with rectal cancer. Firstly, imaging except pelvic CT was evaluated. Secondly, the pelvic CT was evaluated and the staging was adjusted according to the new findings. Subsequently, the two staging results were compared to investigate the added clinical benefit of pelvic CT. Results: Compared with the imaging data except pelvic CT, new findings revealed by the pelvic CT included metastases of the pelvic bone (n = 1) and pelvic peritoneum (n = 3). However, the new findings did not change the primary staging. Of the three patients with pelvic peritoneal metastasis, two were already determined with peritoneal involvement and ascites by abdominal CT, and the third patient was observed with liver and distant lymph node metastasis. Thus, none of their initial stagings needed to be changed. Conclusion: The addition of pelvic CT to the pre-treatment imaging strategy cannot provide added clinical benefit for the primary evaluation of rectal cancer.
Keywords: Rectal cancer